Hydraulic engineering - Xie, Liquan (CRC Press, Taylor & Francis Group, 2013)
Hydraulic Engineering contains 56 technical papers from the 2012 SREE Conference on Hydraulic Engineering (CHE 2012, Hong Kong, 21-22 December 2012, including the second SREE Workshop on Environment and Safety, WESE 2012). The conference served as a major forum for researchers, engineers and manufacturers to share recent advances, discuss problems, and identify challenges associated with engineering applications in hydraulic engineering, and the contributions showcase recent developments in the areas of hydraulic engineering and environmental engineering. - See more at: http://www.betterworldbooks.com/hydraulic-engineering-id-1138000434.aspx&utm_source=Affiliate&utm_campaign=Text&utm_medium=booklink&utm_term=3630151&utm_content=Homepage#sthash.SWSUlgad.dpuf